2012
DOI: 10.1371/journal.pone.0033188
|View full text |Cite|
|
Sign up to set email alerts
|

Symbionts as Major Modulators of Insect Health: Lactic Acid Bacteria and Honeybees

Abstract: Lactic acid bacteria (LAB) are well recognized beneficial host-associated members of the microbiota of humans and animals. Yet LAB-associations of invertebrates have been poorly characterized and their functions remain obscure. Here we show that honeybees possess an abundant, diverse and ancient LAB microbiota in their honey crop with beneficial effects for bee health, defending them against microbial threats. Our studies of LAB in all extant honeybee species plus related apid bees reveal one of the largest co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
496
3
16

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 431 publications
(530 citation statements)
references
References 53 publications
15
496
3
16
Order By: Relevance
“…Isolation of LAB from the fourth instar larval gut in this study assumes significance as the larval gut is the target of highly pathogenic bacteria and fungi. Both royal jelly and worker jelly (bee bread + gland secretions + diluted honey) play an important role in the nature of bacterial composition as reported by Vojvodic et al, (2013) who found that first and second larval instars contained almost exclusively Acetobacteraceae, while later instars were dominated by one or two very different Lactobacillus spp. Acetobacteraceae includes acetic acid bacteria (AAB), a large group of obligate aerobic gram-negative bacteria, well adapted to sugary and alcoholised fluid such as vinegar, fruit juice, sap water, alcoholic beverages and flowers.…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…Isolation of LAB from the fourth instar larval gut in this study assumes significance as the larval gut is the target of highly pathogenic bacteria and fungi. Both royal jelly and worker jelly (bee bread + gland secretions + diluted honey) play an important role in the nature of bacterial composition as reported by Vojvodic et al, (2013) who found that first and second larval instars contained almost exclusively Acetobacteraceae, while later instars were dominated by one or two very different Lactobacillus spp. Acetobacteraceae includes acetic acid bacteria (AAB), a large group of obligate aerobic gram-negative bacteria, well adapted to sugary and alcoholised fluid such as vinegar, fruit juice, sap water, alcoholic beverages and flowers.…”
Section: Resultsmentioning
confidence: 84%
“…Lactobacillus is commonly associated with honey bees even in India (Pattabhiramaiah et al, 2012). Elsewhere L. kunkeei has been reported as the most common fructophilic species (Vasquez et al, 2012). Earlier different species of bacteria have been reported from the pollen (CorbyHarris et al, 2014) and honey stomach (Tajabadi et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations